The Gereja Sebagai Komunitas Inklusi: Refleksi Hidup Menggereja Bersama Penyandang Disabilitas - Paruru, Nofvrind (Institut Agama Kristen Negeri Kupang, 2024)
This article discusses the calling and involvement of the church as a faith community to become an inclusive community as a reflection of the church together with people with disabilities. The method used is a qualitative approach with library methods. Talking about disability also means talking about the body and the human bodily experience. The bodily experience in question is not only a physical matter, but the integrity of humans as bodily beings. The reality of normality which creates a distinction between